Prevalence of Bilateral JOCD of the Knee and Associated Risk Factors. Issue 5 (July 2015) - Cooper, Trenton; Boyles, Aaron; Samora, Walter P.; Klingele, Kevin E.
<x xml:space="preserve">Abstract</x> Purpose: Juvenile osteochondritis dissecans (JOCD) of the knee affects cartilage and subchondral bone surface. Multifocal JOCD is described as multiple lesions within the knee or presence of lesions in other joints. The true prevalence of bilaterality of JOCD is unknown. The purpose of this study is to determine the prevalence of bilateral JOCD and to identify potential risk factors for bilateral disease. Methods: We evaluated 108 consecutive patients presenting for JOCD at a single pediatric hospital system. If an OCD lesion of the knee was found, contralateral knee x-rays were performed. Lesion location was documented according to Cahill and Berg, magnetic resonance imaging (MRI) grading documented according to Dipaola, and if surgical treatment was undertaken, intraoperative grading performed according to Guhl. Patients with unilateral JOCD were compared with those with bilateral disease. Statistical analysis of categorical data was performed utilizing likelihood ratio χ2 test or Fisher exact test and continuous data compared using nonparametric Wilcoxon 2-sample test. Results: There were 85 male (79%) and 23 females (21%) with an average age of 12.3 years (range, 6 to 18 y). Sixty-three percent of lesions were located on the medial femoral condyle and 33% on the lateral femoral condyle. Ninety percent of all lesions were considered weight-bearing lesions. Eighty percent were considered stable on MRI evaluation. Of those lesions that underwent surgical intervention, 61% were either grade I or II lesions. Seventy-three of 108 patients (68%) underwent some form of surgical intervention. Thirty-one patients (29%) were found to have contralateral JOCD lesions. Thirty-nine percent of contralateral lesions found on contralateral radiographs were asymptomatic at presentation and nearly all of those evaluated with MRI (16 of 18) were stable. Sixty-nine percent of contralateral lesions were located on the medial femoral condyle, 27% on the lateral femoral condyle, and 94% were considered weight-bearing lesions. Twelve of 31 contralateral lesions (39%) underwent surgical intervention. Comparing patients with unilateral and bilateral disease, female patients (P<0.05) and younger age at presentation (P<0.009) were risk factors for bilateral JOCD. No statistical difference among other variables was seen with regard to location, MRI or operative stability of lesion, or presence of symptoms. Conclusions: In our consecutive series of 108 patients with JOCD, we found a 29% incidence of bilateral disease. Almost 40% of contralateral lesions were asymptomatic upon presentation. Female sex and younger age at presentation were significant risk factors for bilateral disease. Lesion location, stability, and pain were not statistically significant variables. The authors recommend bilateral radiographic knee evaluation for all patients found to have JOCD. Level of Evidence: Level IV—retrospective case series.